Relaxin-Family Peptide Receptors 1 and 2 Are Fully Functional in the Bovine - Dai, Yanzhenzi; Ivell, Richard; Liu, Xuan; Janowski, Dana; Anand-Ivell, Ravinder (Frontiers in Physiology, 2017)
In most mammals the peptide hormone relaxin is a key physiological component regulating early pregnancy and birth. However synteny analysis shows that the gene encoding ovarian relaxin-2 is deleted in cows and sheep. While these ruminants appear to exhibit a relaxin-like physiology, as in other mammals, until now a molecular understanding of this has been lacking. Cloning and expression analysis of the cognate bovine receptor for relaxin, RXFP1, as well as of the structurally related receptor, RXFP2, in female tissues, shows that these are expressed in a similar way to other mammals. RXFP1 transcripts are found in ovarian theca cells, endometrium and myometrium, whereas RXFP2 transcripts are expressed in ovarian theca cells, oocytes, as well as in myometrium. Transfection of receptor-expressing gene constructs into HEK293 cells indicates that bovine RXFP1 has a greater EC50 at 10-50nM for porcine or human relaxin, compared to human RXFP1. For bovine RXFP2, in contrast, the EC50 is <1nM for its cognate ligand, bovine INSL3, but also 10-30nM for porcine or human relaxin. Functional analysis shows that bovine myometrial cells are able to respond to exogenous relaxin and INSL3 with a significant increase in cAMP. Although expressing mRNA for both RXFP1 and RXFP2, bovine follicular theca cells only respond to INSL3 with a dose-dependent increase in cAMP. Altogether the results suggest that the cow is able to compensate for the missing hormone, and moreover imply that relaxin analogues could offer an important therapeutic option in treating female ruminant infertility.